Specific Absorption Rate Dependency on the Co2+ Distribution and Magnetic Properties in CoxMn1-xFe2O4 Nanoparticles - Venkatesha Narayanaswamy (Nanomaterials, 2021)
Mixed ferrite nanoparticles with compositions CoxMn1-xFe2O4 (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0) were synthesized by a simple chemical co-precipitation method. The structure and morphology of the nanoparticles were obtained by X-ray diffraction (XRD), transmission electron microscope (TEM), Raman spectroscopy, and Mössbauer spectroscopy. The average crystallite sizes decreased with increasing x, starting with 34.9 ± 0.6 nm for MnFe2O4 (x = 0) and ending with 15.0 ± 0.3 nm for CoFe2O4 (x = 1.0). TEM images show an edge morphology with the majority of the particles having cubic geometry and wide size distributions. The mixed ferrite and CoFe2O4 nanoparticles have an inverse spinel structure indicated by the splitting of A1g peak at around 620 cm−1 in Raman spectra. The intensity ratios of the A1g(1) and A1g(2) peaks indicate significant redistribution of Co2+ and Fe3+ cations among tetrahedral and octahedral sites in the mixed ferrite nanoparticles. Magnetic hysterics loops show that all the particles possess significant remnant magnetization and coercivity at room temperature. The mass-normalized saturation magnetization is highest for the composition with x = 0.8 (67.63 emu/g), while CoFe2O4 has a value of 65.19 emu/g. The nanoparticles were PEG (poly ethylene glycol) coated and examined for the magneto thermic heating ability using alternating magnetic field. Heating profiles with frequencies of 333.45, 349.20, 390.15, 491.10, 634.45, and 765.95 kHz and 200, 250, 300, and 350 G field amplitudes were obtained. The composition with x = 0.2 (Co0.2Mn0.8Fe2O4) with saturation magnetization 57.41 emu/g shows the highest specific absorption rate (SAR) value of 190.61 W/g for 10 mg/mL water dispersions at a frequency of 765.95 kHz and 350 G field strength. The SAR values for the mixed ferrite and CoFe2O4 nanoparticles increase with increasing concentration of particle dispersions, whereas for MnFe2O4, nanoparticles decrease with increasing the concentration of particle dispersions. SARs obtained for Co0.2Mn0.8Fe2O4 and CoFe2O4 nanoparticles fixed in agar ferrogel dispersions at frequency of 765.95 kHz and 350 G field strength are 140.35 and 67.60 W/g, respectively. This study shows the importance of optimizing the occupancy of Co2+ among tetrahedral and octahedral sites of the spinel system, concentration of the magnetic nanoparticle dispersions, and viscosity of the surrounding medium on the magnetic properties and heating efficiencies.